Treatment of Intercondylar Humeral Fractures With 3D-Printed Osteosynthesis Plates. Issue 3 (January 2016) - Shuang, Feng; Hu, Wei; Shao, Yinchu; Li, Hao; Zou, Hongxing
Abstract : Abstract: The aim of the study was to evaluate the efficacy custom 3D-printed osteosynthesis plates in the treatment of intercondylar humeral fractures. Thirteen patients with distal intercondylar humeral fractures were randomized to undergo surgery using either conventional plates (n = 7) or 3D-printed plates (n = 6) at our institution from March to October 2014. Both groups were compared in terms of operative time and elbow function at 6 month follow-up. All patients were followed-up for a mean of 10.6 months (range: 6–13 months). The 3D-printing group had a significantly shorter mean operative time (70.6 ± 12.1 min) than the conventional plates group (92.3 ± 17.4 min). At the last follow-up period, there was no significant difference between groups in the rate of patients with good or excellent elbow function, although the 3D-printing group saw a slightly higher rate of good or excellent evaluations (83.1%) compared to the conventional group (71.4%). Custom 3D printed osteosynthesis plates are safe and effective for the treatment of intercondylar humeral fractures and significantly reduce operative time.